High dynamic range imaging using a DMD - Woo, Taeseong; Kim, Hye Yun; Kim, Su Yeon; Hwang, Byungjae; Ahn, Cheolwoo; Kwon, Seok-Kyu; Kim, Jae-Ick; Park, Jung-Hoon (2021 ANNUAL CONFERENCE OF THE IEEE PHOTONICS SOCIETY (IPC), 2021)
In many biological systems, the sample's morphological information cannot be perfectly captured simultaneously by a single image acquisition due to the limited dynamic range of the detector. Here, we propose a high throughput imaging method combined with structured illumination based on a digital micro-mirror device (DMD) to achieve a high dynamic range (HDR). Furthermore, we demonstrate the HDR imaging method enabling depth sectioning by employing HiLo microscopy to the identical experimental system.